Penyuluhan Kesiapsiagaan Gempa Bumi Berpengaruh Signifikan terhadap Kesiapsiagaan Bencana Masyarakat Desa Pusong Kota Lhokseumawe - Yofinda Aurelia Rizkita; Harvina Sawitri; Rizka Sofia (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Indonesia is located at the meeting of the earth's plates, causing catastrophic events, such as earthquakes. Lhokseumawe is one of the cities in Indonesia located in Aceh Province, which has a high potential for the threat of earthquakes. Earthquakes not only cause death, injury, and damage to various health facilities but also have an impact on public health problems. The main factor that causes disasters to cause large casualties and losses is a lack of knowledge about disasters. In this case, health education or counseling can be an important factor that aims to increase public knowledge about disaster preparedness. The purpose of this study was to determine the effect of earthquake disaster preparedness counseling on community preparedness in Pusong Village, Banda Sakti District Lhokseumawe City. This is a quasi-experimental type of research with 150 respondents. Samples were taken using purposive sampling. The results showed that before the extension, the majority of the people were in the medium category (56.0%), while after the extension, the majority of the people were in the high category (67.3%). The Wilcoxon test is used to analyze data. The statistical analysis resulted in a p value of <0.05. The conclusion of this study is that there is a significant effect between earthquake preparedness counseling and community preparedness in Pusong Village, Banda Sakti District, Lhokseumawe City.